Determinan Kualitas Laba pada Isu Pengadopsian International Financial Reporting Standard: Data dari Asia - Utami, Tri; Kusuma, Indra Wijaya (Journal of Accounting and Investment, 2017)
The objectives of this study are to examine the effect of investor protection and ownership structure to the relationship between IFRS adoption and earnings quality in Asian companies. Asia is chosen because it has unique characteristics, one of them is ownership structure in Asia is more concentrated on family. The data from this study is obtained from the OSIRIS database for the periode 2009-2013 in ten Asian Countries (China, Hong Kong, Indonesia, Japan, Korea, Malaysia, Philippines, Singapura, Taiwan dan Thailand). The sample in this study consists of 16.232 firm year observations and Multiple Regression analysis is used to test hypotheses. The results show that the effect of IFRS adoption to earnings quality depend on the level of investor protection in a country. When the investor protection is high, the IFRS adoption results in higher quality of earnings, but when the investor protection is low, there is no effect of IFRS adoption to the earnings quality. The other results also sho, contrary to the predicition, that concentrated ownership structure increases the relationship between IFRS adoption and earnings quality.